5. NUTRITIONAL STATUS AND SOME FACTORS RELATED TO MALNUTRITION AMONG THE ELDERLY AT AN GIANG CENTRAL GENERAL HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2023)
Objectives: Description of nutritional status and some factors related to malnutrition in the elderly at An Giang Central General Hospital in 2023. Subjects and method research: Design cross-sectional descriptive study with an analysis of 260 elderly people in inpatient treatment at An Giang Central General Hospital. Information was collected by a set of prepared questionnaires through face-to-face interviews. Results: Malnutrition in the elderly accounted for 44.2% and women were more malnourished. The study found factors related to malnutrition, such as age, drug use, skin condition and nutritional consumption (p
Keywords: Malnutrition, the elderly.